Fesyen Melalui Media Massa sebagai Pemaknaan Simbolisasi Produk Sosial di Kalangan Remaja Muslim - Hadiati S., Nikmah (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2014)
The process of communication in the consumer culture serves to satisfying needs and delivery of meaning. Due to the changing times, the patterns of communication in relation to the meets of human needs are also changing, so is the goal complicated The phenomenon that frequently arises is the communication through advertising. Advertising is a communication process that is intended to express the mes–sage and image that can give meaning to the products. On the other hand, this process also serves to be a facilitator in the process of exchange of meaning that occurs in social communication. This study focuses on the fashion products. In this context, this research, the domain of social communi–cation, serves to explain social interactions that occur during the process of following these developments, including the social meaning of the symbol of the products.Keywords: social product, meaning, advertising———————————————————————-Proses komunikasi, dalam budaya konsumen, ber–fungsi untuk pemuasan kebutuhan dan penyampaian makna. Akibat perkembangan jaman, pola-pola komunikasi dalam kaitannya dengan pemenuhan kebutuhan manusia juga ber–ubah, sehingga tujuannya kian kompleks. Fenomena yang sering muncul adalah komunikasi melalui periklanan. Per–iklanan adalah proses komunikasi yang bertujuan untuk mengungkapkan pesan dan citra yang dapat memberikan makna terhadap produk. Di sisi lain, proses ini juga ber–fungsi untuk menjadi fasilitator dalam proses pertukaran makna yang terjadi dalam komunikasi sosial. Dalam peneli–tian ini produk yang menjadi fokus perhatian pembahasan adalah produk fesyen. Penelitian dalam domain komunikasi sosial dalam konteks ini berfungsi untuk menjelaskan inte–raksi-interaksi sosial yang terjadi selama proses mengikuti perkembangan tersebut. Pada gilirannya hal ini juga terkait dengan proses pemaknaan simbol sosial produk itu sendiri.Kata Kunci: produk sosial, pemaknaan, iklan